EXPERIENCES OF PEDIATRIC NURSES WORKING WITH COVID-19 INFECTION PATIENTS - Sata, Jintana; Oumtanee, Areewan (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
This phenomenological study utilized Heidegger’s philosophical framework to investigate the lived experiences of pediatric nurses providing care to children diagnosed with COVID-19. A purposive sampling strategy was employed to recruit a sample of 9 professional nurses with experience in caring for children with COVID-19. Data collection methods included in-depth interviews using a semi-structured interview guide, audio recording, observations, and field notes. The data were analyzed using van Manen’s method of phenomenological interpretation. The findings revealed 5 major themes related to the experiences of pediatric nurses caring for COVID-19 patients: 1) the process of admitting pediatric COVID-19 patients for treatment, 2) adapting care practices for pediatric COVID-19 patients, 3) caring for parents infected with COVID-19, 4) COVID-19 infection control measures, and 5) challenges and issues encountered in clinical practice. The results of this study provide essential insights for nursing administrators in managing, planning, and allocating resources to support nurses in the care of pediatric patients with COVID-19. Furthermore, this research offers a foundational perspective for nurses in providing care for patients with COVID-19 or other emerging respiratory infectious diseases in the future.